Bacterial and Archaeal Communities Change With Intensity of Vegetation Coverage in Arenized Soils From the Pampa Biome - Granada, Camille E.; Vargas, Luciano Kayser; Lisboa, Bruno Brito; Giongo, Adriana; Martinho, Caroline Thais; Pereira, Leandro de M.; de Oliveira, Rafael R.; Bruxel, Fernanda; de Freitas, Elisete Maria; Passaglia, Luciane M. P. (Frontiers in Microbiology, 2019)
Arenization occurs in regions that present sandy soils with normal rainfall levels. Predatory use of environmental sources, the dissolution of arenitic rocks and reworking of non-consolidated surface sands intensify this degradation scenario. Thus, this work aimed to evaluate the impact of the arenization process in the Brazilian Pampa Biome and how this phenomenon affects the soil microbial and plant communities. For this purpose, three arenized areas in Southern Brazil (Pampa Biome) were selected and, in each one, three sampling points were studied: arenized (ARA), arenized to grassland transition (AGT) and grassland (GRA) areas. In the three sampling points, soils presented low levels of nutrients, organic matter, clay and pH acidic in all regions but, the presence of vegetation coverage in AGT and GRA areas preserved the topsoil structure. Our study related ARA with bacterial families Alcaligenaceae, Pseudomonadaceae, and Xanthomonadaceae. AGT with bacterial families Bacillaceae and Burkholderiaceae, and plant species Melinis repens (Willd.) Zizka and Paspalum stellatum Humb. & Bonpl. ex Flüggé, and GRA with bacterial families Koribacteraceae, Hyphomicrobiaceae and Chthoniobacteraceae, and plant species Croton subpannosus Müll.Arg. ex Griseb., Piptochaetium montevidense (Spreng.) Parodi and Elyonurus sp.. The three studied areas (as well as sampling points) present soils extremely poor in nutrients with sandy texture, and the bacterial and plant composition well known to be resistant to environmental stresses were dominant. The vulnerability of these areas causes a degradation scenario, which is worsened by agricultural activities. However, in general, this phenomenon is a natural process that occurs mainly due to soil characteristics (poor soils) and climatic variations.